Effect of the Extraction Process on the Biological Activity of Lyophilized Apricot Extracts Recovered from Apricot Pomace - Dina Cheaib; Nada El Darra; Hiba N. Rajha; Iman El-Ghazzawi; Richard G. Maroun; Nicolas Louka (MDPI AG, 2018)
The preservation of polyphenols in fruits by lyophilization has gained great interest in the recent decades. The present study aims to assess the impact of the pre-treatment extraction methods heat-assisted extraction (HAE) and infrared (IR) on lyophilized apricot pomace extracts. Then to test the conservation of polyphenols quantities as well as their bioactivities (antiradical and antibacterial) in lyophilized extract. An aqueous extract was obtained through either heat-assisted extraction or infrared pre-treatments then lyophilized to obtain a dried form. Results showed that the content of polyphenols, the antiradical and antibacterial activities in lyophilized extracts exhibited a slighter decrease in infrared sample compared to the heat-assisted extraction ones. The High-performance liquid chromatography (HPLC) analysis showed that lyophilized extracts IR and HAE preserved the same phenolic molecules (rutin, catechin and epicatechin) detected in liquid extracts (IR and HAE) with a smaller yield. Lyophilization can be used as a widely process in the food industry to conserve many bioactive molecules.